1997
DOI: 10.1021/om960525t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic Characterization, and Reactivity of the Unusual Five-Coordinate Hydrido−Vinylidene Complex OsHCl(CCHPh)(PiPr3)2:  Precursor for Dioxygen Activation

Abstract: The hydrido−carbyne complex OsHCl2(CCH2Ph)(PiPr3)2 (1) reacts with sodium methoxide in 1:1 molar ratio to give the five-coordinate hydrido−vinylidene OsHCl(CCHPh)(PiPr3)2 (2), which affords [OsHCl(CCH2Ph)(H2O)(PiPr3)2]BF4 (3) by reaction with HBF4·H2O. The spectroscopic data obtained for 2 indicate that in solution, it is a mixture of two conformers in equilibrium. The thermodynamic magnitudes involved in the equilibrium as well as the activation parameters for the conversion between them were determined by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 72 publications
5
31
0
Order By: Relevance
“…Indeed, α,β-unsaturated hydroxy-and alkoxy-carbenes are inherently unstable and very few examples of such compounds have been isolated. [10][11][12][13][14][15][16] Accordingly, the apparent stability of 1 in the presence of water and alcohols might be determined predominantly by electronic factors, which is consistent with our observation that both thiols and amines smoothly react with 1 to give isolable α,β-unsaturated thio-and amino-carbene derivatives. 17 On the other hand, the six phenyl substituents at the phosphorus atoms provide remarkable steric congestion at C α and therefore one cannot rule out a steric contribution to the stability of 1.…”
Section: Introductionsupporting
confidence: 90%
“…Indeed, α,β-unsaturated hydroxy-and alkoxy-carbenes are inherently unstable and very few examples of such compounds have been isolated. [10][11][12][13][14][15][16] Accordingly, the apparent stability of 1 in the presence of water and alcohols might be determined predominantly by electronic factors, which is consistent with our observation that both thiols and amines smoothly react with 1 to give isolable α,β-unsaturated thio-and amino-carbene derivatives. 17 On the other hand, the six phenyl substituents at the phosphorus atoms provide remarkable steric congestion at C α and therefore one cannot rule out a steric contribution to the stability of 1.…”
Section: Introductionsupporting
confidence: 90%
“…In agreement with this, it has been observed that, in the presence of a base, the six-coordinate hydride alkylidyne complexes afford five-coordinate hydride vinylidene species. 19 In the current case, the distal amide group prevents the tautomerization of the triple bond as a consequence of the weak coordination of its oxygen atom, which also exerts a directing effect for the hydride migration (path b in Scheme 3 ). Thus, there is an insertion of the triple bond into the Os–H bond of the generated monohydrides, followed by the addition of the proton of the eliminated HCl to the C β atom of the resulting α-substituted alkenyl group, along with the displacement of the coordinated carbonyl group by chloride to give the alkylidene derivatives.…”
Section: Resultsmentioning
confidence: 90%
“…In contrast to the latter, compound 82 eliminates ROH to afford OsHCl(=C=CH 2 )(P i Pr 3 ) 2 (84), which is one of the few five-coordinate hydride-vinylidenes known. 54,55 There is a ring constraint against intramolecular migration to make an alkylidyne when the vinyl ether is cyclic. Thus, the reaction of 10 with 2,3-dihydrofuran gives tetrahydrofuran and the hydride-cyclic carbene derivative 31 (Scheme 31), which is stable in contrast to 81 and 82.…”
Section: C-c Bond Activationmentioning
confidence: 99%